Lexical and semantic processing in the absence of word reading: Evidence from neglect dyslexia - Làdavas, Elisabetta; Umilta, Carlo; Mapelli, Daniela (Neuropsychologia, 1997)
Nine patients with left-sided neglect and nine matched control patients performed three tasks on horizontal (either normal or mirror-reversed) letter strings. The tasks were: reading aloud, making a lexical decision (word vs non-word), and making a semantic decision (living vs non-living item). Relative to controls, neglect patients performed very poorly in the reading task, whereas they performed nearly normally in the lexical and semantic tasks. This was considered to be a dissociation between direct tasks, rather than a dissociation between explicit and implicit knowledge. The explanation offered for the dissociation is in terms of both a dual-route model for reading aloud and a degraded representation of the letter string.